STUDI PARAMETER KUALITAS AIR BAGI KEGIATAN BUDIDAYA LOBSTER (Panulirus sp) DENGAN SISTEM KERAMBA JARING APUNG DI TELUK AMBON DALAM - Louhenapessy, Daniel G; Matakupan, Jolen; Buton, D (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2023)
The demand for lobster on the market is experiencing an upward trend. The utilization of a floating net cage system is a viable opportunity for the cultivation of lobsters in the waters of Inner Ambon Bay. The objective of this study is to examine the water quality parameters associated with the cultivation of Lobster (Panulirus sp.) using a floating net cage system in the Inner Ambon Bay. Water quality parameters encompass a range of physical and chemical factors. Physical characteristics comprise of temperature, salinity, current, and brightness, while chemical parameters include pH, dissolved oxygen (DO), nitrite, nitrate, phosphate, and ammonia. The study was carried out in March 2023 within the seas of Inner Ambon Bay, utilizing a total of 21 designated observation locations. The field measurements encompassed the assessment of many parameters including temperature, salinity, current velocity, dissolved oxygen (DO) levels, pH, and brightness. Additional parameter measurements were conducted at the Maluku Province Health Laboratory Center. The data were analyzed in accordance with government regulations pertaining to the quality standards of sea water for marine biota. According to the findings of the research, the temperature measurements varied between 29 and 30.18°C, the salinity levels ranged from 33.39 - 34 ppt, the pH values spanned from 7 - 10.4, and the dissolved oxygen (DO) concentrations were observed to be between 4.27 and 7.12 milligrams per liter (mg/l). The obtained current velocity values ranged from 8.91 - 24.16 cm/sec, whereas the brightness value ranged from 4.5 - 10.5 m. For the concentration of chemical parameters, the results showed that phosphate ranged values from 0-98.81 mg/l, nitrate 0-0.02 mg/l, while nitrite and ammonia was 0 - 0.01 mg/l and 0 - 0.33 mg/l, respectively. The findings from the data analysis indicate that the overall physical and chemical characteristics of the water meet the established quality standards for marine organisms, particularly in relation to the suitability for sustaining lobsters (Panulirus sp) using a floating net cage system in Ambon Bay. ABSTRAK Permintaan pasar untuk komoditas lobster semakin meningkat. Perairan Teluk Ambon Dalam dapat dikembangkan untuk budidaya lobster dengan menggunakan sistem keramba jaring apung. Penelitian ini bertujuan untuk menganalisis paramater kualitas air bagi kegiatan budidaya Lobster (Panulirus sp) dengan sistem keramba jaring apung di Teluk Ambon Bagian Dalam. Parameter kualitas air meliputi parameter fisik (suhu, salinitas, arus, kecerahan) dan parameter kimia (pH, DO, nitrit, nitrat, fosfat, amonia). Penelitian ini dilakukan pada Maret 2023 di perairan Teluk Ambon Dalam pada 21 titik pengamatan. Parameter suhu, salinitas, arus, DO, pH dan kecerahan diukur secara langsung di lapangan. Sedangkan pengukuran parameter lainnya dilakukan pada Balai Laboratorium Kesehatan Provinsi Maluku. Analisa data menurujuk pada baku mutu air laut untuk biota laut sesuai peraturan pemerintah. Berdasarkan hasil penelitian diperoleh nilai suhu berkisar antara 29-30,18oC, salinitas 33,39- 34 ppt, pH 7-10,4, DO 4,27-7,12 mg/l. Nilai kecepatan arus diperoleh berkisar antara 8,91-24,16 cm/det, sedangkan nilai kecerahan sebesar 4,5-10,5 m. Parameter kimia meliputi fosfat berkisar antara 0,00-98,81 mg/l, nitrat 0,00-0,02 mg/l, nitrit 0,00-0,01 mg/l, dan amonia 0,00-0,33 mg/l. Hasil analisa data menunjukan bahwa parameter fisik dan kimia perairan secara keseluruhan memenuhi standar baku mutu biota laut, khususnya untuk pemeliharaan lobster (Panulirus sp) dengan sistem keramba jaring apung di perairan Teluk Ambon Dalam. Kata Kunci: Teluk Ambon Dalam, keramba jaring apung, lobster, Panulirus sp, kualitas air